LEVEL OF INFLATION AND GDP ON DOMESTIC INVESTMENT IN SOUTH KALIMANTAN OF 2017-2020 PERFORMANCE BASED ON ISLAMIC ECONOMIC PERSPECTIVE - Lisda Aisyah; Zaki Mubarak; Halimatus Sa'diah; Muhammad Ramadhani (Journal of Management and Islamic Finance, 2022)
This research aims to determine and analyze the effect of the inflation rate and GDP on domestic investment levels in South Kalimantan. This type of research is a quantitative research with data collection methods used are secondary data in the form of time series data taken from the official website of BPS South Kalimantan. The research sample used was for 4 years from 2017 until 2020 period. To test the hypothesis, this research uses multiple linear regression analysis method through the Eviews 9 program. The results obtained in this study indicate that the inflation rate and GDP variable are able to explain the variable domestic investment of 14.35% and the remaining 85.65% explained by other variables outside the research. In the F-test, the inflation rate variable and GDP variable has a significant effect on the domestic investment variable. Then at the t-test, the inflation rate variable has a negative effect on the domestic investment variable. Meanwhile, the GDP variable has a positive effect and significant on the domestic investment variable.